Szerb próbálkozás a Bánság kikerekítésére : egy, az 1860-as évekből való etnikai alapú területkikülönítési terv társadalomelméleti vonatkozásai - Pap, Tibor (Közép-Európai Közlemények, 2010)
After the disappearance of Serbian Voivodina and the Temesi Bánság, Serbian political agents in the Habsburg Empire found that restarting the dialog with the Hungarian political elite is the inevitable next move in order to reach their set ethnopolitical aims. This turn had a particular 'program' to bring into effect, the so-called round-out plan. Its essence was to make the Hungarian majority and administration accept the (ethnically based) forming of one or two large-counties on the concerned territories. This text presents the ideological-conceptual background and the discursive embeddedness of the related Serbian ideas. The researcher attemps to reevaluate the whole of the process along the lines of Luhmann's social theory (more precisely by the change of ruling form and code theorem). Thus, the structural anomalies of this set of problems (thematized in the political discourse of the age as an ethnical issue) will be shown in a different light.